Typography on drink more water posters / Nurhafizira Mohd Razali - Mohd Razali, Nurhafizira (2019)
I declare that the wor Water is essential. It plays an important role in us as it covered up to 70% of the human adult body. It regulates the body temperature, blood circulatory, digestion and endocrine system. Human body uses water in all its cells, organs, and tissues to help maintain other bodily functions too. It is important to rehydrate by drinking plenty on plain water and eating foods that contain water because the body loses water through breathing, sweating, and digestion. The amount of water we need depends on a variety of factors, how physically active we are and whether we are experiencing an illness or have any other health problems. The purpose of this research is to identify about typography used in posters of drink more water and improvise it at the end of this research as to deliver the message successfully to the audience and ensure acknowledge the society. Three basic elements of typography will be used throughout this research and they are color, alignment and typeface. The criticism will be made by using Feldman method of art criticism.